Constituintes químicos de licania tomentosa Benth. (Chrysobalanaceae) Chemical constituents of Licania tomentosa Benth. (Chrysobalanaceae) - Rachel Oliveira Castilho (Química Nova, 2008)
This paper describes the chemical constituents isolated from leaves and fruits of Licania tomentosa Benth. The plant materials were successively extracted with hexane and methanol. From the extracts the following compounds were obtained: betulinic acid; licanolide, a new triterpene lactone; oleanolic acid, lupeol; palmitoleic and hexadecanoic acid; a mixture of stigmasterol and sitosterol; and a mixture of tormentic, ursolic and betulinic acid. The structures of the natural products were identified on the basis of spectral data.